DA’WAH TRANSFORMATION IN THE DIGITAL AGE: (STUDY ON HUBBUL WATHAN GRAND MOSQUE, NTB) - Sri Ayu Rayhaniah; Andik Riyanto; Ashrun Mubarak Malik (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2025)
This research was initiated due to the rapid development of information technology that has influenced religious activities, including mosque-based da’wah. The Hubbul Wathan Grand Mosque in West Nusa Tenggara is an example of a religious institution that has been able to adapt to digitalization. Using a qualitative approach, this study analyzes the transformation of traditional da’wah into digital da’wah using Everett M. Rogers' Innovation Diffusion theory. The results of the study show that the process of da'wah transformation takes place gradually, starting from collective consciousness to the publication of digital-based da'wah. Digital da'wah has been proven to expand the reach of the congregation, increase religious interaction, and strengthen the image of the mosque as a center for modern Islamic da'wah. This study recommends increasing the digital capacity of mosque administrators and policy support that encourages the digitization of da'wah.